Exploring the Effect of Mechanical Damage on the Water State in Blueberries Using Low-Field Nuclear Magnetic Resonance Spectroscopy - LUO Zixuan, JIANG Fengli, WU Peijing, SONG Ping, DING Keke (Shipin Kexue)
In this study, a custom apparatus was utilized to obtain blueberry samples with high and low levels of mechanical injury (DI and DII group), which were subsequently stored at 4 or 25 ℃ and analyzed using low-field nuclear magnetic resonance (LF-NMR) spectroscopy. Spectroscopic data and proton density images were collected at 0, 6, and 24 h post-damage. The results demonstrated a significant impact of injury on the water state and distribution of blueberries. Notably, the cell wall water content A21 decreased, whereas the cytoplasm water content A22 increased over time post-damage. The A22 of the high injury group increased by 1.45 times at 24 h compared with that at 0 h, while the vacuole water content A23 and the total water content A2 notably declined, indicating a rapid redistribution and transfer of water from damaged blueberries to the external environment. As the degree of damage increased, the major peak of vacuole water shifted to the right and decreased significantly. Furthermore, increasing storage temperature further exacerbated these changes. At 25 ℃, the emergence of 4 relaxation peaks at both 6 and 24 h after damage indicated a significant deterioration in the quality of blueberries. Compared with 25 ℃, storage at 4 ℃ was more conducive to maintaining fruit integrity and slowing down the rate of moisture loss from damaged blueberries. The experimental results provide a theoretical basis and data reference for the rapid detection and mechanistic understanding of mechanical damage in blueberries.